The Reliability and Validity of the Center for Epidemiologic Studies Depression Scale (CES-D) for Chinese University Students - Jiang, Lijun; Wang, Ying; Zhang, Yining; Li, Rui; Wu, Huailiang; Li, Chenyi; Wu, Yunlin; Tao, Qian (Frontiers in Psychiatry, 2019)
Aims: Depression is prevalent among university students worldwide, and the prevalence appears to be increasing. As an intermediate stage between healthy and depression, students with subthreshold depression could develop worsening depression or be recovered with intervention to prevent depression. The Center for Epidemiologic Studies Depression Scale (CES-D) is a useful tool to assess subthreshold depression. The primary purpose of the current study was to evaluate the psychometric characteristics of CES-D in Chinese university students. Secondly, we aimed to describe the prevalence of subthreshold depression among the student sample and examine its demographic correlates. Methods: A total of 2,068 university students participated in the study, and they were asked to respond to the Chinese CES-D, Beck Depression Inventory-II (BDI-II), and Positive and Negative Affect Schedule (PANAS). The reliability was assessed by calculating Cronbach's α, inter-item correlation, and item-total correlation coefficients. The factor structure was evaluated by conducting exploratory (EFA) and confirmatory factor analysis (CFA) using a structural equation modeling approach. The prevalence of subthreshold depression was calculated and the demographic correlates of gender, grade, and major were examined by multiple regression. Results: The final sample included 1,920 participants. The prevalence of subthreshold depression among university students reached 32.7% with a cut-off score of 20 for the 20-item CES-D and 31% with a cut-off of 16 for the 14-item CES-D, although there was no significant difference of prevalence in gender, grade, and major. The EFA results suggested extraction of three factors (somatic symptoms, negative affect, and anhedonia) that account for 52.68% of total variance. The CFA results suggested that the newly derived model with 14 items was the best fit with our data. Six items were finally removed from the original scale (item 9, 10, 13, 15, 17 and 19). The Cronbach’s alpha of the 14-item CES-D was 0.87. Conclusions: The CES-D has good reliability and validity for assessing subthreshold depression in Chinese university students.